Recalcitrant pollutants removal from paper mill wastewater by ferrous ion- and heat- activated persulfate oxidation processes using response surface methodology: a comparison study - Guvenc, Senem Yazici; Can-Guven, Emine; Varank, Gamze (TAYLOR & FRANCIS INC, 2022)
In this study, the removal of UV254, phenol, and calcium from paper industry wastewater by persulfate oxidation was investigated. Fe2+ addition and heat application methods were used for persulfate activation. Response surface methodology and central composite design were applied for the optimization of effective parameters on processes. The statistical fit of the model was confirmed by the high R-2 and adjusted R-2 values. Based on the results obtained, response surface methodology models were developed. Estimated results calculated with model equations and experimental data were close to each other, and the models were confirmed to be significant. As a result of experimental studies conducted under the optimum conditions determined by the model, UV254, phenol, and calcium removal efficiencies from paper industry wastewater were 84.2%, 92.6%, and 85.7%, respectively by the Fe2+-activated persulfate process while they were 96.4%, 96.3%, and 81.8%, respectively by heat-activated persulfate process. The results of the study showed that persulfate oxidation is an effective advanced treatment process for recalcitrant pollutants removal from paper industry wastewater and response surface methodology is a useful tool for optimizing the treatment parameters.
Keywords: Calcium; CCD; paper industry wastewater; persulfate oxidation; phenol; UV254; ZERO-VALENT IRON; ELECTRO-FENTON; STATISTICAL OPTIMIZATION; HETEROGENEOUS CATALYSTS; PROCESS PARAMETERS; AQUEOUS-SOLUTIONS; COD REMOVAL; PULP; DEGRADATION; INDUSTRY; Chemistry; Engineering